Front Cover: Hydrophobic deep eutectic solvent‐based microextraction method for the simultaneous extraction of two benzodiazepines from saliva samples before determination by 96‐well microplates‐based spectrophotometer with the aid of chemometrics. Issue 9 (5th September 2022) - Heidari, Hassan; Sadi, Sevda
Abstract : DOI: 10.1002/sscp.202200060 The cover picture shows the microextraction steps of two benzodiazepines, clonazepam and nitrazepam, from the saliva sample using a green solvent based on a deep eutectic solvent. A back‐extraction method was used to retrieve the drugs from the deep eutectic solvent phase to the aqueous solution and a 96‐well microplates‐based spectrophotometer with the aid of the partial least squares approach was used for the simultaneous determination of the drugs.